A Profile of Exemplary Teachers of English for Young Learners at The Elementary School - Rahmad Husein (Pascasarjana UM, 2014)
Abstract: This study portrayed a profile of exemplary EYL teachers’ competence indicators of pedagogical and professional implementation and personal and social manifestation. The research involved seven subjects. The data were collected through interviews, observations, field-notes and documentary studies and they were analyzed by a snowballing procedure. The study found out that the subjects performed professional competences which classified them as exemplary EYL teachers at the elementary school. The findings also revealed that professional development along with personal and social competences contributed much to the teachers’ pedagogical competences. Key Words: competence, teacher’s competences, english for young learners (EYL), EYL teacher, elementary school Abstrak: Penelitian ini menggambarkan indikator kompetensi contoh profil guru EYL dalam implementasi pedagogis dan profesional dan perwujudan secara pribadi dan sosial. Penelitian ini melibatkan tujuh subjek. Data dikumpulkan melalui wawancara, observasi, catatan lapangan dan studi dokumentasi. Data kemudian dianalisis dengan metode snowballing. Studi ini menemukan bahwa subjek melakukan kompetensi profesional yang diklasifikasikan sebagai guru EYL di sekolah dasar yang perlu dicontoh. Temuan juga mengungkapkan bahwa pengembangan profesional bersama dengan kompetensi pribadi dan sosial menyumbang banyak untuk kompetensi pedagogis guru.Kata kunci: kompetensi, kompetensi guru, bahasa Inggris untuk pemula (EYL), guru EYL, SD